1972
DOI: 10.2307/3799054
|View full text |Cite
|
Sign up to set email alerts
|

Barred Owl Habitat Use as Determined by Radiotelemetry

Abstract: Radio transmitt ers were successfu lly placed on 10 barred owls (Strix varia) during 59.65-66 and the movemen ts of the owls were followed with an automatic radio-tra cking system for a total of 1,182 days. More than 28,000 owl locations were sampled from some two million locations recorded. These locations , along with habitat availabil ity informati on, were programme d for computer analysis to determine intensity of habitat use. Barred owls showed consisten t and highly significa nt preferenc e or avoidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…In eastern deciduous forests, they are typically found in mature and old, mixedwood swamps and riparian areas (Nicholls and Warner 1972, Elody and Sloan 1985, Bosakowski et al 1987. In boreal forest of Saskatchewan (Mazur et al 1998) and foothills forest in western Alberta (Takats 1998), Barred Owls selected old mixedwood (white spruce (Picea glauca) and trembling aspen (Populus tremuloides), aspen, and balsam poplar forest.…”
Section: Introductionmentioning
confidence: 99%
“…In eastern deciduous forests, they are typically found in mature and old, mixedwood swamps and riparian areas (Nicholls and Warner 1972, Elody and Sloan 1985, Bosakowski et al 1987. In boreal forest of Saskatchewan (Mazur et al 1998) and foothills forest in western Alberta (Takats 1998), Barred Owls selected old mixedwood (white spruce (Picea glauca) and trembling aspen (Populus tremuloides), aspen, and balsam poplar forest.…”
Section: Introductionmentioning
confidence: 99%
“…Mazur et al (1997b) used a similar small-scale plot (11.3 m radius) with the nest tree at the centre, and reported a somewhat higher mean percentage cover of 57% (Sd 17); this was not significantly different from random plots. Other studies reported yet higher percentage canopy cover within larger Barred Owl home ranges: 96% (Se 1.1) (haney 1997), 62.8% (Winton and leslie 2004), utilized "dense" cover disproportionately (no values given) (Nicholls and Warner 1972), >66% (Grossman et al 2008), and >56% (Singleton et al 2010).…”
Section: Nest Tree Species Percentage Canopy Cover and Forest Standmentioning
confidence: 92%
“…it is therefore unlikely that Barred Owls choose a nest site based on tree species per se. high percentage forest canopy cover has been cited as a determining factor in Barred Owl selection of breeding habitat, possibly because it provides solar insulation (Nicholls and Warner 1972;haney 1997;Winton and leslie 2004;Grossman et al 2008), but the influence of forest canopy may depend on the size of the area that was measured. in this study, canopy cover was measured within a 30 m circular plot centered on the nest tree, and it did not appear to influence Barred Owl nest tree habitat use: more than half the sample had a canopy cover of ≤50% (Table 2).…”
Section: Nest Tree Species Percentage Canopy Cover and Forest Standmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimated annual home ranges of nine radio-tagged barred owls studied by Nicholls and Warner (1972) averaged 231 hectares, and varied from 86 to 370 hectares. The estimated annual home ranges of seven owls similarly tracked by Elody and Sloan (1985) averaged 282 hectares, but during the summer months only about 118 hectares of the overall home range were used.…”
Section: Habitats and Ecologymentioning
confidence: 99%